Work‐Related Stress Is Associated With Unfavorable Cardiovascular Health: The Multi‐Ethnic Study of Atherosclerosis - Oluseye Ogunmoroti; Olatokunbo Osibogun; Norrina B. Allen; Victor Okunrintemi; Yvonne Commodore‐Mensah; Amit J. Shah; Erin D. Michos (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Work‐related stress is a psychosocial risk factor linked to a higher risk of cardiovascular disease. However, the association between work‐related stress and cardiovascular health (CVH) is not well established. We estimated the association between work‐related stress and CVH in a multiethnic sample of adults free of cardiovascular disease at baseline. Methods and Results We performed a cross‐sectional analysis of 3579 community‐based men and women, aged 45 to 84 years, of the Multi‐Ethnic Study of Atherosclerosis from data collected between 2000 and 2002. Work‐related stress (yes/no) was assessed by a self‐administered questionnaire. CVH was measured by the American Heart Association's Life's Simple 7 metrics (smoking, physical activity, body mass index, diet, total cholesterol, blood pressure, and blood glucose). Each metric contributed 0, 1, or 2 points if in the poor, intermediate, or ideal range, respectively. The aggregated CVH score was 0 to 14 points and categorized as inadequate (0–8 points), average (9–10 points), and optimal (11–14 points). Polytomous logistic regression was used to estimate the association between work‐related stress and CVH, adjusting for sociodemographic factors. The mean±SD age was 57±8 years, and 48% were women. Work‐related stress was reported by 20% of participants. In fully adjusted models, participants with work‐related stress had lower odds of having average (adjusted odds ratio [OR], 0.75 [95% CI, 0.62–0.92]) and optimal (adjusted OR, 0.73 [95% CI, 0.58–0.92]) CVH scores compared with participants without work‐related stress. Conclusions Work‐related stress was associated with unfavorable CVH. These findings underscore the importance of workplace psychological well‐being and suggest the need for studies on interventions that may reduce work‐related stress and promote CVH.